Leadership Style in Relation to Gender Role and Masculine Values: Being Daoist Water‐Like or Agentic?. Issue 4 (23rd February 2022) - Zhou, Wen‐Qian; Lee, Yueh‐Ting; Jacobs, Eric
Abstract : Based on the Daoist water‐like theory in relation to leadership and gender, the current study aims to compare two leadership styles (Daoist water‐like and Agentic) and their relation to the gender role of leaders and the masculine values of perceivers. A 2 × 2 × 2 between‐subjects factorial experiment (leader gender, leadership style, and perceiver masculinity value) was conducted to examine the favorability, empowerment, and democracy (FED) of the leader by using vignettes as stimulus materials. Participants ( N = 383) were recruited from MTurk and were randomly assigned to evaluate the leader candidate in the vignette. Overall, the results indicated that Daoist water‐like leadership was perceived as more FED than agentic leadership. Moreover, Daoist water‐like male leadership was seen as the most FED, while the agentic male leadership style was seen as the least FED. Finally, perceivers with low masculine values tended to view the Daoist water‐like leadership as more FED than agentic leadership, while perceivers with high masculine values did not endorse agentic over Daoist water‐like leadership. Implications of the Daoist water‐like leadership in relation to the gender role of the leader and masculine values of the perceiver are discussed.